2020
DOI: 10.1038/s41419-020-02927-7
|View full text |Cite
|
Sign up to set email alerts
|

ASC modulates HIF-1α stability and induces cell mobility in OSCC

Abstract: High-level expression of ASC (Apoptosis-associated speck-like protein containing a CARD) leads to lymph node metastasis in OSCC, but the underlying mechanism remains unclear. Here, we show that HIF-1α participates in ASCinduced metastasis. We identified 195 cell-motion-associated genes that were highly activated in ASC-overexpressed SAS_ASC cells; of them, 14 representative genes were found to be overexpressed in OSCC tissues in our previously reported RNA-seq dataset, OSCC-Taiwan. Nine of the 14 genes were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…As an adaptive response to hypoxic stress, hypoxic tumor cells activate several survival pathways to carry out their essential biological processes compared with normal cells. The hypoxia-inducible factor-1α (HIF-1α) is one crucial facilitator for energy adaption and oxygen metabolic stress in hypoxia and nutrition deficiency tumor environment, and functions as a general regulator of tumor aggressiveness and metastasis as well [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an adaptive response to hypoxic stress, hypoxic tumor cells activate several survival pathways to carry out their essential biological processes compared with normal cells. The hypoxia-inducible factor-1α (HIF-1α) is one crucial facilitator for energy adaption and oxygen metabolic stress in hypoxia and nutrition deficiency tumor environment, and functions as a general regulator of tumor aggressiveness and metastasis as well [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to versatile functions in inflammasomeindependent biological processes (195)(196)(197)(198)(199)(200), ASC has established its central role in inflammasome signaling. Briefly, ASC connects the inflammasome sensor and caspase-1 via homotypic interactions of CARD-CARD and PYD-PYD, hierarchically organizing and densely packing the ternary inflammasome complex into a micrometer-sized disk-like structure that is denoted a pyroptosome or an ASC speck.…”
Section: Asc-mediated Inflammasome Assemblymentioning
confidence: 99%
“…Furthermore, the same HIF-1α can be regulated by NLRP3. In this case, it has been observed that the adaptor protein ASC associates and stabilizes HIF-1α to increase cell migration and metastasis in oral squamous cell carcinoma [ 78 ]. However, other investigations demonstrate that hypoxia may be a repressor of NLRP3.…”
Section: Mitochondrial Dysfunction and Inflammation In Cvds And Cancermentioning
confidence: 99%